Faktor – Faktor yang Mempengaruhi Harga Saham dengan Struktur Modal Sebagai Variabel Intervening (Studi Empiris Perusahaan yang Tergabung dalam LQ 45 Periode Tahun 2015 – 2017) - Subadriyah Subadriyah; Mukaromah Mukaromah (Jurnal Rekognisi Akuntansi, 2019)
This research aims to analyze factors that affect stock prices with capital structure as intervening variables in companies incorporated in LQ45 for the period 2015-2017. This research uses dependent variables namely Stock Price, independent variables Sales Growth, Profitability, Liquidity, and intervening variables Capital Structure7. Sampling techniques are purposive sampling method, obtained samples as many as 28 manufacturing companies and using multiple linear regression and expanded with path analysis, as well as tests to determine the influence of each independent variable using the t-tes) and coefficient of determination using IBM SPSS version 23. The results showed that sales growth and capital structure had no direct effect on stock prices, profitability had a direct positive effect on stock prices, liquidity had a direct negative effect on stock prices. In this study also obtained the results of sales growth did not affect the stock price indirectly through the capital structure as an intervening variable, profitability did not have an indirect effect on the stock price through the capital structure as an intervening variable, and liquidity did not affect the stock price indirectly on the stock price through the capital structure as an intervening variable.